Genomic Insights Into Sugar Adaptation in an Extremophile Yeast Zygosaccharomyces rouxii - Guo, Hong; Qiu, Yue; Wei, Jianping; Niu, Chen; Zhang, Yuxiang; Yuan, Yahong; Yue, Tianli (Frontiers in Microbiology, 2020)
The osmotolerant Zygosaccharomyces rouxii is known for its trait to survive in extreme high sugar environments. This ability determines its role in the fermentation process and leads to yeast spoilage in the food industry. However, our knowledge of the gene expression in response to high sugar stress remains limited. Here, we conducted RNA-sequencing (RNA-seq) under different sugar concentrations of the spoilage yeast, Z. rouxii, which exhibit extremely high tolerance to sugar stress. The obtained differentially expressed genes (DEGs) are significantly different to that of the Saccharomyces cerevisiae, which is sensitive to extreme high sugar stress. Most of the DEGs participated in the “glucan synthesis,” “transmembrane transport,” “ribosome,” etc. In this work, we also demonstrated that the gene ZYRO0B03476g (ZrKAR2) encoding Kar2p can significantly affect the growth of Z. rouxii under high sugar stress. In addition, we combined with a previous study on the genome sequence of Z. rouxii, indicating that several gene families contain significantly more gene copies in the Z. rouxii lineage, which involved in tolerance to sugar stress. Our results provide a gene insight for understanding the high sugar tolerance trait, which may impact food and biotechnological industries and improve the osmotolerance in other organisms.